2019
DOI: 10.1098/rspa.2019.0460
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing synchrony in multiplex network due to rewiring frequency

Abstract: Most of the previous studies on synchrony in multiplex networks have been investigated using different types of intralayer network architectures which are either static or temporal. Effect of a temporal layer on intralayer synchrony in a multilayered network still remains elusive. In this paper, we discuss intralayer synchrony in a multiplex network consisting of static and temporal layers and how a temporal layer influences other static layers to enhance synchrony simultaneously. We analytically derive local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 30 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…For instance, in a network of Hindmarsh-Rose neurons in which the coupling structure of both electrical and chemical synapses is time-varying, it has been found that the coupling strength required for the achievement of complete synchrony is significantly lower for increasing the rewiring frequency 50 . Moreover, the enhancement effect has been also observed in a network with multiple layers in which only the structure of specific layers is time-varying 51 . Furthermore, it has been shown that diverse partial synchronization patterns can be generated by multi-plexing of adaptive networks 52 .…”
mentioning
confidence: 90%
“…For instance, in a network of Hindmarsh-Rose neurons in which the coupling structure of both electrical and chemical synapses is time-varying, it has been found that the coupling strength required for the achievement of complete synchrony is significantly lower for increasing the rewiring frequency 50 . Moreover, the enhancement effect has been also observed in a network with multiple layers in which only the structure of specific layers is time-varying 51 . Furthermore, it has been shown that diverse partial synchronization patterns can be generated by multi-plexing of adaptive networks 52 .…”
mentioning
confidence: 90%
“…Multiplex network is a subclass of multilayer networks, where one-to-one interactions between all the nodes in different layers are maintained [15], [16]. In recent time, collective dynamics in multi-layered networks has been extensively explored [15], [1], [17], [18], [19], [20], [21], [22] including investigations on chimera states [23], [24] and explosive synchronization [25], [26]. In such multilayer dynamical networks [27], [28], [29], synchrony is one of the most important desired states for all practical purposes since it is essential for the efficient performance of the networks.…”
Section: Introductionmentioning
confidence: 99%
“…These synchronized states can emerge as the effect of the static or time-varying interactions in either attractive or repulsive couplings [19]. Moreover, enormous effort has been devoted to the controllability and observability of synchronized complex networks [20], improving the synchronizability [21,22] and robustness of synchronization [23].…”
mentioning
confidence: 99%